2017
DOI: 10.3389/fpsyg.2017.02010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diglossia on Word and Non-word Repetition among Language Impaired and Typically Developing Arabic Native Speaking Children

Abstract: The study tested the impact of the phonological and lexical distance between a dialect of Palestinian Arabic spoken in the north of Israel (SpA) and Modern Standard Arabic (StA or MSA) on word and non-word repetition in children with specific language impairment (SLI) and in typically developing (TD) age-matched controls. Fifty kindergarten children (25 SLI, 25 TD; mean age 5;5) and fifty first grade children (25 SLI, 25 TD; mean age 6:11) were tested with a repetition task for 1–4 syllable long real words and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 89 publications
(157 reference statements)
1
10
0
Order By: Relevance
“…These studies showed that the acquisition of reading, and of related phonological processing skills, is impacted by the phonological distance between SpA and StA, both in impaired and in typically developing readers. Research has also endorsed the debilitative impact of phonological distance on letter naming (Asaad & Eviatar, 2013) and on phonological memory in typically developing and in children with developmental language disorder (Saiegh- Haddad & Ghawi-Dakwar, 2017). Altogether, the results from these studies suggest difficulty among Arabic-speaking children in developing high-quality phonological representations for StA words.…”
Section: Diglossia and Phonological Processing In Arabicmentioning
confidence: 87%
See 1 more Smart Citation
“…These studies showed that the acquisition of reading, and of related phonological processing skills, is impacted by the phonological distance between SpA and StA, both in impaired and in typically developing readers. Research has also endorsed the debilitative impact of phonological distance on letter naming (Asaad & Eviatar, 2013) and on phonological memory in typically developing and in children with developmental language disorder (Saiegh- Haddad & Ghawi-Dakwar, 2017). Altogether, the results from these studies suggest difficulty among Arabic-speaking children in developing high-quality phonological representations for StA words.…”
Section: Diglossia and Phonological Processing In Arabicmentioning
confidence: 87%
“…Note that the unique words used in the current study were a combination of unique words encoding StA phonemes and those not encoding StA phonemes. Earlier research has shown that unique words that do not encode StA phonemes are easier to process in memory (using a nonword repetition task) than unique words that do not encode StA phonemes (Saiegh-Haddad & Ghawi-Dakwar, 2017). This factor may turn out to be important in clarifying some of the underlying differences in phonological representation between cognates and different types of unique words, and is a question is for future research to pursue.…”
Section: Discussionmentioning
confidence: 97%
“…In parallel, several studies have reported schizophrenia-related reading deficits (Whitford et al, 2018), including those implicated in diglossia, such as impaired phonological awareness (Revheim et al, 2006). Similarly, diglossia and schizophrenia have both been separately associated with the reduced ability in performing word and nonword repetition tasks (Farnam et al, 2015;Saiegh-Haddad and Ghawi-Dakwar, 2017), implying a common deficit in verbal working memory. A working memory dysfunction is proposed to be a fundamental impairment leading to thought disorder in schizophrenia (Deserno et al, 2012;Goldman-Rakic, 1994).…”
Section: Diglossia and Language Developmentmentioning
confidence: 97%
“…Children also have difficulties in recognizing the MSA phonemes that are absent from their colloquial varieties, and the production of such MSA phonemes is considerably delayed (Amayreh, 2003;Saiegh-Haddad, 2007;Saiegh-Haddad, Levin, Hende, & Ziv, 2011). Phonological distance between MSA and colloquial varieties also impacts word and nonword repetition both in typically developing children and in children with specific language impairment (Saiegh-Haddad & Ghawi-Dakwar, 2017). In the same vein, a forced-choice grammaticality judgement study in Palestinian Arabic strongly suggested that full mastery of morphosyntactic structures of MSA was still not in place at the fifth grade (Khamis-Dakwar, Froud, & Gordon, 2012).…”
Section: The Current Studymentioning
confidence: 99%